Data on growth performance, proximate composition, and fatty acid content of edible oyster (Crassostrea spp.), farmed on shellstring along Cox's Bazar Coast - Tashrif Mahmud Minhaz; Joyshri Sarker; Mohammed Nurul Absar Khan; Helena Khatoon; Md Abdul Alim; SM. Khalequzzaman; Moin Uddin Ahmad; Mohammad Redwanur Rahman (Data in Brief, 2020)
Data on growth performance, proximate composition and fatty acid content of Edible oysters (Crassostrea spp.) were collected to evaluate the spatial variation in growth performance, proximate composition and fatty acid content of oyster. The oyster was farmed on shellstring for 120 days in the three sites: Nunia chara, Chowfoldandy and Sonadia Island. Oysters were marked into six different age classes: T1: 31—45 days; T2: 46—60 days; T3: 61—75 days; T4: 76—90 days; T5: 91—105 days and T6: 106—120 days. Data on environmental variables were collected in every 15 days. Oysters were collected for physical measurements and biochemical analysis after 120 days. Data on growth performance showed spatial variation. Withal, data on proximate composition and fatty acid content were significantly different (p < 0.05) among the three sites. This data could contribute in oyster aquaculture development.